'New wine in new bottles': class politics and the 'uneven electrification' of colonial India. Issue 1 (2nd January 2018) - Chatterjee, Animesh
ABSTRACT: The introduction of electricity supply into urban colonial India in the late-nineteenth and early twentieth centuries coincided with the emergence of an Indian middle class debating its own identity and autonomy, and the development of 'modern' and Westernised urban centres. This article examines how colonial plans for urban and domestic electrification were influenced by the class politics of the urban Indian middle class and its varied notions of nationalism, traditionalism and modernity. I investigate how the colonial government and promoters of electrical technologies responded to the opportunities and constraints of the urban Indian middle-class domestic sphere to refashion the language of electricity to be contiguous with the political and social exigencies of the emerging Indian middle class. Looking at the language of electrification that arose in the social, cultural and political contexts reveals how far class and identity politics were matters of importance in what has been termed 'the uneven electrification of the British empire'. While this article concentrates on urban colonial India, it brings to light newer aspects of the place of electricity within processes of urban development and class politics, and vice versa, especially within the unsettled cultural and social backgrounds of colonial societies.